Secure Kernel Execution with Intel SGX - Meneguele, Bruno; Fonseca, Keiko; Rosa, Marcelo (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2020: Anais Estendidos do X Simpósio Brasileiro de Engenharia de Sistemas ComputacionaisDO - 10.5753/sbesc_estendido.2020.13108, 2020)
Intel SGX is not accessible from the most privileged execution level, known as ring zero, where the operating system kernel is placed. However, it is possible to split the execution responsibility between kernel and userspace by creating a dependency among these two levels that allow internal kernel data to be stored or processed within SGX private enclaves. In this paper we present SKEEN, an enhanced way to isolate internal operating system components and structures with Intel SGX technology, preventing information leak to different components of the same operating system. A proof-of-concept is provided to exemplify its usage.